The role of CCR6 rs 3093024 in Rheumatoid Arthritis patients in Iraq (Journal of Pharmaceutical Negative Results, 2022)
Rheumatoid arthritis (RA) is a chronic auto immune and inflammatory disease of obscure etiology. But the emergence of disease is mostly influenced by genetic, immunological, and environmental factors. This study was investigated the polymorphisms of SNP (rs3093024) of CCR6 gene and its association with susceptibility to RA, serum level of the chemokine CCR6 also were investigated to determine its association with RA disease. Accordingly, a case-control analysis was carried out on 60 patients with RA and 30 healthy control. The ELISA result indicated that the CCR6 mean was increased highly significant in the serum of RA patient than the serum level of control (299.19 ± 17.12 versus 149.52 ± 5.36pg/ml, p=0.0001**). For CCR6 rs3093024 A>G logistic regression analysis result revealed that both of the alleles (A and G) and genotypes (AA, AG and GG) was not associated with susceptibility to RA in the present sample of Iraqi patients.